Overview and Correlation Between Work Stress and Dry Eyes Syndrome among Nurses in Indonesia - Rondhianto; Siswoyo; Annisa Putri Zalsabila (KHD-Production, 2024)
Exhausted nurses in providing nursing care can impact work stress. Many factors cause work stress. Work stress is the type of psychological stress that reduces the lacrimal gland's activity, affecting dry eye syndrome. The study aims to analyze the correlation between work stress and nurses' dry eye syndrome in Nganjuk General Hospital. The study was a descriptive correlative observational with a cross-sectional design. The sample was 84 nurses, taken by simple random sampling. Data were collected using Health and Safety Executive (HSE) and Ocular Surface Disease (OSDI) questionnaires. The study showed nurses experienced mild stress (96.43%) and moderate dry eye syndrome (36.90%). There was a positive correlation between work stress and dry eye syndrome in nurses in the weak category (r=0.356; p= 0.001< 0.05). There were no significant differences in work stress by age, gender, working period, and marital status (p=0.388; p=0.687 p=0.730; p = 0.839 > α 0.05). There was a significant difference in work stress based on education (p=0.033 < α 0,05). There were no significant differences in dry eye syndrome with age, gender, working period, and marital status (p=0.644; p=0.436; p= 0.865; p=0.072; p=0.719 > α 0,05). The study conclusion is that work stress is related to dry eyes syndrome. Apart from that, work stress is also influenced by the level of education. Therefore, interventions to reduce work stress in nurses should pay attention to education level to reduce the risk of dry eyes syndrome.